The Inhibitory Effects of Rosmarinic Acid on RANKL-Mediated Osteoclastogenesis, F-actin Ring Formation and Bone Resorption through the Suppression of the NF-κB Signaling Pathway - Kasekarn, Waraporn (Trends in Sciences, 2025)
The hyperactivation of osteoclasts is crucial in the process of bone degradation, leading to alterations in pathological bone resorption. The inhibition of excessive osteoclastogenesis and bone resorption through bioactive compounds derived from natural sources could represent an effective strategy for prevention or treatment. Rosmarinic acid (RA), a naturally occurring phenolic compound found in various aromatic plants, exhibits promising biological activities and therapeutic potential against multiple diseases. This study aimed to clarify the inhibitory effects and molecular mechanisms of RA on RANKL-induced osteoclastogenesis in RAW 264.7 cells. Treatment with RA at a non-toxic concentration resulted in a significant reduction in both the number of osteoclasts observed in TRAP staining and TRAP enzymatic activities. Quantitative real-time PCR analysis of mRNA gene expression revealed that RA significantly downregulated the expression of seven osteoclast-specific markers, including TRAF6, TRAP, NFATc1, c-Fos, Cathepsin K, MMP-9, and DC-STAMP. Furthermore, western blot analysis demonstrated that RA significantly suppressed the expression of osteoclast-specific proteins such as TRAF6, NFATc1, c-Fos, Cathepsin K, MMP-9, and DC-STAMP, as well as the phosphorylation of IκBα and NF-κB p65 signaling proteins. Additionally, RA was found to reduce F-actin ring formation and the area of bone resorption pits. In conclusion, RA effectively inhibits osteoclastogenesis, F-actin ring formation, and bone resorption by suppressing the NF-κB signaling pathway. These findings suggest that RA could serve as an active ingredient in dietary supplements for diseases related to osteoclast activity, such as osteoporosis. HIGHLIGHTS Rosmarinic acid inhibits RANKL-induced osteoclastogenesis in RAW 264.7 cells. Rosmarinic acid suppresses the TRAF6/NF-kB signaling pathway in RANKL-mediated osteoclastogenesis. Rosmarinic acid down-regulates the gene and protein expression of osteoclast-specific markers during osteoclastogenesis. Rosmarinic acid decreases the F-actin ring formation and bone resorption. GRAPHICAL ABSTRACT